Content analysis of Published Articles in Sport Mont in the Period from 2003 - 2020 in the Field of Combat Sports - Pavle Malovic (Journal of Anthropology of Sport and Physical Education)
When it comes to sports science, it is inevitable to mention the Sport Mont Journal, which has an 18 years long respectable tradition, and which is progressing every year. Sport Mont was founded in 2003 as the official journal of the Montenegrin Sports Academy (MSA), by all merit to the great vision of a full professor at the Faculty for Sport and Physical Education, Dusko Bjelica. The Sport Mont, which is published in three editions annually (February, June, and October), records over 1.400 papers from almost all fields of sports science and sports medicine, signed by renowned scientists from all around the world. During a period of 18 years in Sport Mont is published 120 scientific papers on the topic of combat sports. It can be said that the biggest number of published articles about the mentioned topic was published in 2005 (17), and the activity of scientists from the field of combat sports was quite low in the last couple of years of existence Sport Mont. In 2020 is published 5 scientific papers in a topic of combat sports and it is the bigger number in comparison to the last couple of years, so it seems that authors from the field of combat sports are again active as in the period when Sport Mont established and there is hope that they will give a contribution to developing Sport Mont journal in the next period. This research can be useful for further theoretical research, as well as for theoreticians.